2017
DOI: 10.1038/s41598-017-16411-4
|View full text |Cite
|
Sign up to set email alerts
|

The O-specific polysaccharide lyase from the phage LKA1 tailspike reduces Pseudomonas virulence

Abstract: Pseudomonas phage LKA1 of the subfamily Autographivirinae encodes a tailspike protein (LKA1gp49) which binds and cleaves B-band LPS (O-specific antigen, OSA) of Pseudomonas aeruginosa PAO1. The crystal structure of LKA1gp49 catalytic domain consists of a beta-helix, an insertion domain and a C-terminal discoidin-like domain. The putative substrate binding and processing site is located on the face of the beta-helix whereas the C-terminal domain is likely involved in carbohydrates binding. NMR spectroscopy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 92 publications
4
85
0
Order By: Relevance
“…distal end of gp38 (discussed below). The central b helix alone has a similar structure to the b helices found in various phage TSPs, e.g., Salmonella phages P22 (Steinbacher et al, 1996) and Det7 (Walter et al, 2008) as well as Shigella (Freiberg et al, 2003), Pseudomonas (Olszak et al, 2017), and E. coli phages (Prokhorov et al, 2017). Superimposition with the P22 TSP (RMSD = 3.0 Å for 86 residues, DALI Z score = 3.9) revealed striking similarities between these two topologically diverse RBPs ( Figure 3C).…”
Section: Similarities Of the Gp38 Central B Helix With Phage Tspsmentioning
confidence: 66%
“…distal end of gp38 (discussed below). The central b helix alone has a similar structure to the b helices found in various phage TSPs, e.g., Salmonella phages P22 (Steinbacher et al, 1996) and Det7 (Walter et al, 2008) as well as Shigella (Freiberg et al, 2003), Pseudomonas (Olszak et al, 2017), and E. coli phages (Prokhorov et al, 2017). Superimposition with the P22 TSP (RMSD = 3.0 Å for 86 residues, DALI Z score = 3.9) revealed striking similarities between these two topologically diverse RBPs ( Figure 3C).…”
Section: Similarities Of the Gp38 Central B Helix With Phage Tspsmentioning
confidence: 66%
“…Accordingly, phages can be highly specific for a given O antigen serotype, or can have a broader host range if they recognize more conserved constituents of LPS [137]. A number of LPS-specific phages that target P. aeruginosa have been described in the literature as well as phage-resistant mutants arising from mutations in LPS biosynthesis genes [138][139][140][141][142][143][144][145][146][147]. In other cases, phage resistance may arise when temperate bacteriophages encode proteins that modify the O antigen, conferring resistance to superinfection [148].…”
Section: Phages and Pyocinsmentioning
confidence: 99%
“…These enzymes may be useful in developing novel narrow-spectrum antimicrobial therapies [151]. For instance, Olszak et al showed that a polysaccharide lyase from phage LKA1 degrades P. aeruginosa serotype O5 OSA, and this sensitized bacteria to serum complement, reduced virulence in a wax moth larvae infection model, and disrupted biofilms [147].…”
Section: Phages and Pyocinsmentioning
confidence: 99%
“…The effect of a tail spike protein (LKA1gp49) encoded by Pseudomonas phage LKA1 on P. aeruginosa PAO1 strain pathogenicity has also been evaluated in the G. mellonella model. Whether by administering the protein after larval infection or by incubating it with the bacterium an hour before infection, a greater survival rate than the untreated groups was observed during the 72h infection period [67].…”
Section: Pseudomonas Aeruginosa (P Aereuginosa)mentioning
confidence: 99%